A fourth-order solution-adaptive finite-volume algorithm for compressible reacting flows on mapped domains - Owen, Landon, author; Gao, Xinfeng, advisor; Guzik, Stephen, committee member; Marchese, Anthony, committee member; Estep, Donald, committee member (Colorado State University. Libraries, 2019)
Accurate computational modeling of reacting flows is necessary to improve the design combustion efficiency and emission reduction in combustion devices, such as gas turbine engines. Combusting flows consists of a variety of phenomena including fluid mixing, chemical kinetics, turbulence-chemistry interacting dynamics, and heat and mass transfer. The scales associated with these range from atomic scales up to continuum scales at device level. Therefore, combusting flows are strongly nonlinear and require multiphysics and multiscale modeling. This research employs a fourth-order finite-volume method and leverages increasing gains in modern computing power to achieve high-fidelity modeling of flow characteristics and combustion dynamics. However, it is challenging to ensure that computational models are accurate, stable, and efficient due to the multiscale and multiphysics nature of combusting flows. Therefore, the goal of this research is to create a robust, high-order finite-volume algorithm on mapped domains with adaptive mesh refinement to solve compressible combustion problems in relatively complex geometries on parallel computing architecture. There are five main efforts in this research. The first effort is to extend the existing algorithm to solve the compressible Navier-Stokes equations on mapped domains by implementing the fourth-order accurate viscous discretization operators. The second effort is to incorporate the species transport equations and chemical kinetics into the solver to enable combustion modeling. The third effort is to ensure stability of the algorithm for combustion simulations over a wide range of speeds. The fourth effort is to ensure all new functionality utilizes the parallel adaptive mesh refinement infrastructure to achieve efficient computations on high-performance computers. The final goal is to utilize the algorithm to simulate a range of flow problems, including a multispecies flow with Mach reflection, multispecies mixing flow through a planar burner, and oblique detonation waves over a wedge. This research produces a verified and validated, fourth-order finite-volume algorithm for solving thermally perfect, compressible, chemically reacting flows on mapped domains that are adaptively refined and represent moderately complex geometries. In the future, the framework established in this research will be extended to model reactive flows in gas turbine combustors.
Keywords: computational fluid dynamics; high-order finite-volume methods; detonations; compressible reacting flows